2024
DOI: 10.1002/ccd.30947
|View full text |Cite
|
Sign up to set email alerts
|

Combined ultrasound and angiographic guidance to facilitate transradial access procedures

Francesco Bianchini,
Marco Lombardi,
Alfredo Ricchiuto
et al.

Abstract: The introduction of transradial access for percutaneous coronary diagnostic and interventional procedures has led to a decrease in access site complications. The aim of this paper is to propose a combined stepwise technical approach where real time ultrasound (“echo‐first” approach) can be used to select the best vascular access and, together with angiography, to manage the potential obstacles that may occur during transradial procedures. In each section, we summarize some tips and tricks based on both our exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Most of the data on upfront GP IIb/IIIa inhibitors administration are limited to the pre-P2Y12 antagonists era, and nowadays, their routine use is no longer recommended [52] . Recent studies conducted in the era of potent P2Y12 inhibitors have shown conflicting results regarding the benefits of GP IIb/IIIa inhibitors, raising concerns about an increased risk of thrombocytopenia and bleeding events [47,53] . Shortening the infusion duration of GP IIb/IIIa inhibitors to less than 18-24 h, as tested in most prior trials, may be considered safer in patients at low risk of bleeding, especially when PCI is performed via a radial approach [54] .…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Most of the data on upfront GP IIb/IIIa inhibitors administration are limited to the pre-P2Y12 antagonists era, and nowadays, their routine use is no longer recommended [52] . Recent studies conducted in the era of potent P2Y12 inhibitors have shown conflicting results regarding the benefits of GP IIb/IIIa inhibitors, raising concerns about an increased risk of thrombocytopenia and bleeding events [47,53] . Shortening the infusion duration of GP IIb/IIIa inhibitors to less than 18-24 h, as tested in most prior trials, may be considered safer in patients at low risk of bleeding, especially when PCI is performed via a radial approach [54] .…”
Section: Pharmacological Managementmentioning
confidence: 99%